Frequency distribution of acute abdominal pain causes in patients referred to Shahid Sadoughi hospital, Yazd, Iran - Shiryazdi, Seyed Mostafa; Azhdari, Azadeh; Fallahzadeh, Hossein (Medicinski časopis, 2019)
Introduction Acute abdominal pain is the most common complaints to visit the emergency room. It can be caused by a wide range of underlying surgical and non-surgical conditions. These patients need a quick assessment because of the probability of conducting surgery. The aim of this study was to evaluate the frequency distribution of acute abdominal pain reason and its relation with age, underlying disease and sex. Materials and Methods This descriptive cross sectional study was conducted on 352 patients with acute abdominal pain in Shahid Sadoughi hospital. Data were extracted from medical records. Diagnosis of disease was performed by physician. Results The most common underlying disease in patients with acute abdominal pain was hypertension (14.8٪) and diabetes mellitus (10.8(٪. The most common cause of disease was related to abdominal pain without any cause (32.2٪), intestinal obstruction (14.8%), appendicitis (13.1%), cholecystitis (11.1%) and lead poisoning (4%). The most symptoms in these patients were nausea (49.7٪), vomiting (48.6(٪, persistent pain (61.6(٪ and reduced appetite (49.7٪). There was significant difference between frequency distribution of acute abdominal pain causes in terms of age, sex, job and marital status (p